Beyond Thrombus Level: Increased Surgical Complexity, Nutritional Status, and Postoperative Complications Shape Outcomes in Renal Cell Carcinoma with Venous Tumor Thrombus—A 14-Year Single-Center Experience - Zuzanna Korbecka; Beata Jabłońska; Michał Serafin; Wiktoria Kuczmik; Bartosz Pomianowski; Karolina Blady; Robert Król (Cancers, 2026)
Background: Renal cell carcinoma (RCC) with venous tumor thrombus (VTT) (RCC-VTT) represents a surgically challenging entity with heterogeneous prognosis. While the level of thrombus has traditionally been considered a key prognostic factor, its independent impact remains controversial. Aim: The aim of the study was to evaluate perioperative and oncological outcomes in patients with RCC-VTT, as well as to assess the impact of VTT level on the surgical and oncological outcomes, and identify predictors of postoperative complications and overall survival (OS). Material and Methods: A retrospective analysis of patients who underwent radical nephrectomy with thrombectomy for RCC-VTT between 2012 and 2025 was performed. Patients were stratified into two groups based on thrombus level: low-level (VTT 1) vs. high-level (VTT 2–4) according to Neves–Zincke classification. Clinical, laboratory, and pathological variables were analyzed. Predictive factors for postoperative complications and OS were identified using logistic regression analysis and Cox regression analysis. Results: A total of 235 patients were included, with 123 in the low-level group and 112 in the high-level group. Patients with higher VTT level had significantly higher NRS 2002 score (3 vs. 4, p < 0.001) and lower preoperative hemoglobin levels (12.21 vs. 11.15 g/dL, p < 0.001). High-level VTT was associated with longer operative time (median: 107.5 vs. 125 min, p = 0.06), increased blood loss (264.11 vs. 599.18 mL, p = 0.001), increased red blood cells transfusion (0.69 vs. 1.46 units, p < 0.001) and higher rate of major complications (Clavien–Dindo ≥III: 19 (33.33% vs. 12.50%, p < 0.001)). In multivariate analysis, VTT level was not an independent predictor both for postoperative complications. In the multivariate model, the NRS 2002 (OR = 4.90, 95% CI = 2.53–9.48, p < 0.001) and blood loss (OR = 1.002, 95% CI = 1.001–1.003; p < 0.001) proved to be an independent predictive factors for postoperative complications. In multivariate Cox proportional hazard regression analysis, including only preoperative parameters, the NRS 2002 (HR = 1.44, 95% CI = 1.04–1.99, p = 0.03) and N1-2 (HR = 1.67, 95% CI = 1.07–2.61, p = 0.02) were independent predictive factors of OS. Conclusions: Higher VTT level was associated with increased surgical complexity, including longer operative time, greater blood loss, and higher transfusion requirements, but was not an independent predictor of OS. VTT level was not an independent predictive factor for OS. Long-term survival was independently associated with nutritional status (NRS 2002), and lymph node involvement.